2000
DOI: 10.1146/annurev.biophys.29.1.497
|View full text |Cite
|
Sign up to set email alerts
|

Electrostatic Mechanisms of DNA Deformation

Abstract: The genomes of higher cells consist of double-helical DNA, a densely charged polyelectrolyte of immense length. The intrinsic physical properties of DNA, as well as the properties of its complexes with proteins and ions, are therefore of fundamental interest in understanding the functions of DNA as an informational macromolecule. Because individual DNA molecules often exceed 1 cm in length, it is clear that DNA bending, folding, and interaction with nuclear proteins are necessary for packaging genomes in small… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

11
195
0

Year Published

2000
2000
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 169 publications
(206 citation statements)
references
References 101 publications
11
195
0
Order By: Relevance
“…For N e ) 4, this structure is derived from the average ensemble structures for 50 ensembles. 1 DNH, and DHH in one alignment medium), and 3 JH3′-P restraints but differ in the representation of the nonbonded interactions. 1GIP employs a simple repulsive van der Waals term coupled with the base-base positional database potential of mean force and the multidimensional torsion-angle database potential of mean force (13), while 1DUF uses Lennard-Jones van der Waals and electrostatic potentials (12).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For N e ) 4, this structure is derived from the average ensemble structures for 50 ensembles. 1 DNH, and DHH in one alignment medium), and 3 JH3′-P restraints but differ in the representation of the nonbonded interactions. 1GIP employs a simple repulsive van der Waals term coupled with the base-base positional database potential of mean force and the multidimensional torsion-angle database potential of mean force (13), while 1DUF uses Lennard-Jones van der Waals and electrostatic potentials (12).…”
Section: Resultsmentioning
confidence: 99%
“…Solution NMR methods have also provided structural insights into DNA (5,9,10). One approach has sought to derive very precise single structures (precision of e0.2 Å) using extensive NMR data, including not only traditional NOE-derived short (<5 Å) interproton distance restraints but also residual dipolar coupling (RDC) 1 and 31 P chemical shift anisotropy (CSA) restraints (11)(12)(13)(14)(15). The most recent of these studies suggested that although a very precise structure could be generated that satisfied the experimental data reasonably well, there was evidence of conformational heterogeneity at the level of the deoxyribose sugars since the sugar RDCs could not be fully accounted for within experimental error (15).…”
mentioning
confidence: 99%
“…This structure may be rather regular due to the homogeneity of DNA backbone [9,10]. The ordering of counterions around DNA macromolecule determines the elastic properties of the double helix (bending, twisting, denaturation), DNA interaction with biologically active compounds (proteins, drugs), and compaction mechanisms of macromolecule in small volumes (chromosomes, viral capsids) [11][12][13][14][15][16]. The study of dynamical ordering of DNA counterions is of paramount importance for understanding the mechanisms of DNA biological functioning.…”
Section: Introductionmentioning
confidence: 99%
“…DNA-ligand binding | DNA packaging | atomic force microscopy | atomistic simulations | Poisson-Boltzmann equation E lectrostatic forces have long been recognized to inherently influence the DNA structure and interactions (1,2) including DNA bending and folding (3,4), DNA packaging (5-7), and DNA-ligand recognition (8)(9)(10), owing to the high charge density of the DNA molecule. In particular, the crucial role of coulombic forces in the binding affinity of molecules to a specific DNA sequence, such as clinically important drugs into minor grooves (9) and protein complexes into major grooves (11), has been well established (12).…”
mentioning
confidence: 99%